The potential role of irisin in the thermoregulatory responses to mild cold exposure in adults. Issue 5 (23rd March 2016) - Calton, Emily K.; Soares, Mario J.; James, Anthony P.; Woodman, Richard J.
Abstract : Objectives: To determine the acute effect of a mild cold exposure on thermoregulatory thermogenesis and the role of circulating irisin in the process. Methods: We studied 22 adults (9 males, 13 females) aged 57.7 ± 10.07 years and body mass index 27.8 ± 4.52 kg/m 2 . Participants experienced a 90‐min exposure to 20°C and 25°C in a randomized cross‐over design. Resting metabolic rate (RMR), forearm to finger‐tip gradient (FFG), blood pressure (BP), in‐the‐ear temperature (IET), and fasting bloods were measured on each occasion. Results: There were significant increases in FFG [mean ± SD: +3.8 ± 3.0°C, P < 0.001], systolic blood pressure (SBP) [+8 ± 13 mm Hg, P = 0.015], and diastolic blood pressure (DBP) [+4 ± 6 mm Hg, P = 0.005] and decreases in IET [−0.24 ± 0.29°C, P = 0.001]. Overall, RMR [+190 ± 570 kJ/d, P = 0.135], irisin, glucose or insulin did not differ between temperatures. There were no significant between‐gender differences, but males significantly increased SBP (+12 ± 16, P = 0.02) and DBP (+6 ± 7, P = 0.02) with decreases in heart rate (−4 ± 3, P = 0.002), while females did not. Moreover men had approximately 50% higher thermogenic response while women had approximately 25% greater vasoconstrictor response. Adjusted for age, gender, insulin sensitivity, and body composition, fold changes in irisin were inversely related to respiratory quotient ( r = −0.54, P = 0.048), while IET was related to FFG ( r = −0.55, P = 0.043). Conclusions: Mild cold exposure increased vasoconstriction with a drop in IET and these were related. Greater irisin was related to a greater fasting fat oxidation in the absence of shivering. A potential gender bias in thermoregulation was noted. Am. J. Hum. Biol. 28:699–704, 2016. © 2016 Wiley Periodicals, Inc.